Facilitating patient-oncologist communication in advanced treatment-resistant cancer: development and feasibility testing of a question prompt list - A. Rault; S. Dolbeault; J. Terrasson; C. Bouleuc; P. Cottu; S. Piperno-Neumann; M. Rodrigues; P. Vaflard; A. Brédart (Pilot and Feasibility Studies, 2024)
Abstract Background Patients’ expectations regarding medical information in advanced stages of cancer are still poorly understood. Tailoring information to advanced cancer patients is a subtle task. We developed a question prompt list (QPL) that serves as a patient-oncologist communication aid in France. Methods A four-step sequential mixed method involving patients with luminal B/triple-negative metastatic breast cancer or metastatic uveal melanoma (N = 110) and patients’ partners, oncologists, and researchers (N = 18) was used. In-depth interviews and questionnaires focused on the information needed at the disclosure of metastasis or resistance to treatment (step 1), the formulation of questions and procedures for use in oncology visits (steps 2 and 3), and the acceptability of the final tool (stage 4). Results The initial version of the QPL consists of 17 questions covering 5 themes (disease, current treatment, other options, living with cancer, prognosis). In step 2, 13 questions were added, 2 were merged, and 5 were deleted; a short form (4 questions) and recommendations for clinical use were proposed. In step 3, 2 questions were merged, and 6 were deleted. Four oncologists (27% of the target population) took part in step 4, and the QPL was discussed with 20 patients, revealing a positive appraisal. Conclusion We provide a rigorously developed, relevant, concise, and acceptable question prompt list for clinical application in the advanced cancer care setting in France. Further research needs to assess whether this tool actually facilitates oncologist–patient communication and improves satisfaction with care and health outcomes. Trial registration The study is listed on ClinicalTrials.gov (NCT04118062) and registered under identification n° IRRID “International Registered Report Identifier”: DERR1-10.2196/26414.